2016
DOI: 10.17957/ijab/15.0125
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Crop Water Stress of Rice using Infra-red Thermal Imager under Water Deficit Condition

Abstract: A thermal imager was used for measuring the canopy temperature to calculate crop water stress index (CWSI) of rice under water deficit condition. The CWSI varied diurnally with peaks appeared at noon, and soil water deficit led to higher CWSI values during noon. Transpiration rate (Tr), stomatal conductance (gs) and net photosynthetic rate (Pn) were high at low CWSI, and reduced with increasing CWSI. The relationship between CWSI and Pn, Tr or gs at noon was described by quadratic polynomial equations. At crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
(49 reference statements)
3
20
1
5
Order By: Relevance
“…The latter is a good indicator of cotton water stress and is preferable to transpiration rate. In addition, some studies have shown that relationship between CWSI and crop physiological indicators (stomatal conductance or transpiration rate) is non-linear [8,14,50,51]. In this paper, we further analyzed and pointed out that the relationship between CWSI and crop physiological indicators was a linear model, and to some extent, linear relationship was superior to non-linear model relationship.…”
Section: Discussionmentioning
confidence: 88%
“…The latter is a good indicator of cotton water stress and is preferable to transpiration rate. In addition, some studies have shown that relationship between CWSI and crop physiological indicators (stomatal conductance or transpiration rate) is non-linear [8,14,50,51]. In this paper, we further analyzed and pointed out that the relationship between CWSI and crop physiological indicators was a linear model, and to some extent, linear relationship was superior to non-linear model relationship.…”
Section: Discussionmentioning
confidence: 88%
“…The user must also bear in mind that relationships between thermal readings and water-stress-related physiological variables must be determined to properly evaluate the information provided by thermal imagery [66,75]. The literature provides examples on the use of ground-based thermal imagery to detect water status changes in a variety of plants, from ornamental [76] to herbaceous [59,77] and woody crops [57,68,78].…”
Section: Ground-based Imagerymentioning
confidence: 99%
“…Infrared thermal imaging was used to identify drought-tolerant lentil genotypes, validating it as a high-throughput screening tool in plants (Biju et al 2018). In addition, the thermal imaging was proven to be a reliable method for water deficit diagnosis by measuring the canopy temperature (Xu et al 2015). Hyperspectral imaging, another nondestructive technique, is widely used in agriculture (Lowe et al 2017).…”
Section: Introductionmentioning
confidence: 99%